Structural, electronic, magnetic, elastic and thermodynamic properties of Ni4N anti-perovskite. (3rd August 2021) - Azouaoui, A.; El haoua, M.; El Hamdani, I.; Benzakour, N.; Haboubi, K.; Hourmatallah, A.; Rezzouk, A.
ABSTRACT: We have analyzed the structural, electronic, magnetic, elastic and phonon properties of N i 4 N anti-perovskite by using density functional theory (DFT) based on the generalized gradient approximation scheme and Monte Carlo simulations within the Ising model. The structural investigation exposes the ferromagnetic configuration stability of the compound. Also, the density of states (DOS) and band structure calculations show a metallic behavior of N i 4 N . The investigated elastic constants, phonon dispersion and density phonon states showed that the N i 4 N compound is mechanically and dynamically stable. We also found that the N i 4 N is ductile from the Poisson's ratio, Pugh's ratio and Cauchy pressure. The thermodynamic parameters like heat capacity, Debye and melting temperature have also been calculated. The critical exponents of N i 4 N obtained by Monte Carlo simulation are highly in agreement with the 3D-Ising model around the critical temperature T C . The obtained value of T C agrees reasonably well with available experimental and theoretical works.